- Title: Title: Serum Ceramide Species and Meteorin-Like Protein as a Novel Combined Biomarker Panel for the Diagnosis of Early-Stage Type 2 Diabetes Mellitus: Novel Combined Biomarker Panel for the Diagnosis of Early-Stage Type 2 Diabetes Mellitus - Zhao , Xiaoyu; Pulatov , Muhriddin; Kurbanova , Shakhlokhon (Journal of Medical Biochemistry, 2026)
Background: The identification of biomarkers reflecting early pathophysiological changes in Type 2 Diabetes Mellitus (T2DM) is crucial for timely intervention. Ceramides, lipotoxic sphingolipids, and Meteorin-like protein (Metrnl), an insulin-sensitizing adipomyokine, are mechanistically linked to T2DM development.Aims: To compare serum levels of specific ceramides (Cer-16, Cer-18, Cer-24, Cer-24:1) and Metrnl between T2DM patients and controls, and to evaluate their individual and combined diagnostic accuracy.Methods: This case-control study included 80 newly diagnosed T2DM patients and 80 age- and BMI-matched normoglycemic controls. Fasting serum was analysed for standard biochemical parameters. Ceramide species were quantified by LC-MS/MS. Serum Metrnl was measured via ELISA.Results: The T2DM group exhibited significantly elevated levels of Cer-16 (p
Keywords: Type 2 Diabetes Mellitus; Biomarkers; Ceramides; Sphingolipids; Meteorin-like protein; Insulin Resistance; Lipotoxicity.